Knowledge of tuberculosis and associated health-seeking behaviour among rural Vietnamese adults with a cough for at least three weeks - Hoa, Nguyen Phuong; Thorson, Anna E K; Long, Nguyen Hoang; Diwan, Vinod K (Scandinavian journal of public health. Supplement, 2003)
Good general lay knowledge of tuberculosis (TB), its cause and treatment is considered important for both prompt healthcare seeking and adherence to treatment. The main aim of this study was to describe the knowledge of TB among med and women with a cough for more than three weeks and to see how their health seeking related to TB knowledge. A population-based survey was carried out within a demographic surveillance site in Vietnam. The study population included 35,832 adults aged 15 years or over. Cough cases were identified at household level and structures interviews were carried out with all cases of cough in person. A total of 559 people (1.6%) reported coughing with a duration of three weeks or longer (259 men and 300 women). A large proportion of individuals with a cough for more than three weeks had limited knowledge of the causes, transmission modes, symptoms, and curability of TB. Men had a significantly higher knowledge score than women (3.04 vs 2.55). Better knowledge was significantly related to seeking healthcare and seeking hospital care. More men than women did not take any health care action at all. Health education for TB thus seems to be useful, but efforts must be made to ensure that both men and women in different socioeconomic contexts can access the information.